Engineering with nature: a systematic review, nature-based solutions (NBS) and hybrid coastal protection - Hamsan, Muhammad Amirul Syafiq; Ramli, Muhammad Zahir; Jefri Din, Mohammad ikhmal Siddiq; Ariffin, Effi Helmy; Ibrahim, Izihan; Ibrahim, Saerahany Legori; Razali, Muhammad Rizal (Zibeline International Publishing Sdn. Bhd., 2026)
Coastal communities worldwide are facing increasing threats from climate change induced hazards such as sea-level rise, storm surge and particularly erosion which are having a negative impact on environmental, economic and socio-cultural stability. Traditional hard structure usually gives immediate mitigation to reduce this problem but they often disrupt the ecosystem and paradigm shift towards nature-based solutions (NbS) and hybrid systems receive a positive response around the world. The rapid evolutions of coastal protection strategies are necessary for a comprehensive review to understand the effectiveness, trends and benefits of NbS and hybrid systems. This systematic literature review (SLR) fills these gaps by synthesizing recent studies to guide resilient coastal adaptation in the face of increasing climate challenges. NbS and hybrid systems offer sustainable, resilient coastal protection with hybrid balancing the ecological benefit and structure reliability. A review of 88 articles from 2020 - 2025 from Scopus and ScienceDirect showed the increasing pathway of this research with mainly publication from Europe and Asia. Field studies and numerical modelling revealed NbS effectively reduces erosion and wave energy in moderate conditions while hybrid systems enhance resilience during extreme events and significantly stabilize the shoreline. The hybrid system approaches provide robust, multifunctional solutions and climate goals. These findings advocate for policy reforms, interdisciplinary collaboration and expand research in underrepresented countries/regions to foster equity and sustainable coastal adaptation strategies.